Description of physical preparedness of rural children 10–12 years comparative with persons the same of age in 1985 year. - Грабик, Н. М. (Slobozhanskyi Herald of Science and Sport, 2011)
In the article is compared physical preparedness of rural boys and girls 10–12 years with persons the same of age in 1985 year. As a result of research advantage of schoolboys of the present is exposed above the persons the same of age in 1985 on the indexes of speed, adroitness, speed-power possibilities. At the 10–12-years-old boys of the pas the better developed power possibilities. The schoolgirls of the present yield to the persons the same of age in 1985 as a result of jump length from a place. Research is conducted within the limits of the Ternopil region.